1988
DOI: 10.1002/bit.260310503
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure—temperature bioreactor for studying pressure—temperature relationships in bacterial growth and productivity

Abstract: Thermophilic organisms offer many potential advantages for biotechnological processes; however, realization of the promise of thermophiles will require extensive research on bacterial thermophily and high-temperature cultivation systems. This article describes a novel bioreactor suitable for precise studies of microbial growth and productivity at temperatures up to 260 degrees C and pressures up to 350 bar. The apparatus is versatile and corrosion resistant, and enables direct sampling of both liquids and gase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Deep down in the Martian subsurface, pressures will be greater than 1 bar, even reaching 300 bar at the lowest subsurface depth where calculations suggest that liquid water can exist (Mellon and Phillips, 2001), and any resident life forms would have to deal with those pressures. High-pressure effects on microbial growth, including a methanogen, Methanococcus jannaschii, have been reported (Miller et al, 1988). The results showed that M. jannaschii demonstrated similar methane production rates at 7.8 and 100 bar using a high-pressure-temperature bioreactor.…”
Section: Discussionsupporting
confidence: 51%
“…Deep down in the Martian subsurface, pressures will be greater than 1 bar, even reaching 300 bar at the lowest subsurface depth where calculations suggest that liquid water can exist (Mellon and Phillips, 2001), and any resident life forms would have to deal with those pressures. High-pressure effects on microbial growth, including a methanogen, Methanococcus jannaschii, have been reported (Miller et al, 1988). The results showed that M. jannaschii demonstrated similar methane production rates at 7.8 and 100 bar using a high-pressure-temperature bioreactor.…”
Section: Discussionsupporting
confidence: 51%
“…For studies at elevated hyperbaric pressure, M. jannaschii was grown in a high-pressure, high-temperature reactor system described elsewhere (21), with the following modifications. To minimize exposure of the culture to potentially reactive metal surfaces, a removable glass liner was fitted inside the stainless steel vessel (25).…”
Section: Methodsmentioning
confidence: 99%
“…Beside the extraction, high pressure and temperature perturb bacterial growth (Miller et al, 1988); promote hydrothermal synthesis of graphite tubes (Libera and Gogotsi, 2001) and the synthesis of several compounds (Awana et al, 2007;Marre et al, 2009). To the best of our knowledge HPTE has not been systematically used for polyphenols extraction.…”
Section: Introductionmentioning
confidence: 99%